Perancangan Dan Implementasi Sistem Informasi Urunan Desa (URDES) Berdasarkan Pada Pajak Bumi Dan Bangunan - Iwan Sidharta; Mirna Wati (STMIK Mardira Indonesia, Bandung, 2015)
Urunan Desa (URDES) is an imposition of levies in the form of a sum of money to the villagers with a particular classification, with the services provided by the village government or form of participation of rural communities in supporting the implementation of rural development and village government organization magnitude value based on the results of consultation and agreement between the government village with BPD (Badan Pemusyawarahan Desa) is taken from the calculation of the principal provisions of the property tax each taxpayer. However, the low percentages of taxpayers still lower the level of tax receipts and URDES. In addition because there is widespread awareness of the public to pay taxes, the lack of a system intended for taxpayers who want to know the necessary information about the taxpayer's property tax as well as the village and used data processing and reports that are running currently using Microsoft Excel. Based on the phenomenon than designed and implemented Information System Based on Percentage URDES Property Tax using descriptive and Waterfall system development methods, other than that this final project using Visual Studio 2005, Microsoft Access 2007 as database and operating system Windows XP. The expected result of this system that software can help users in the preparation of reports required by this system and to facilitate the presentation of information systems URDES percentage of the amount of property tax. Keywords: sytem information; tax property